Abortion in Sweden and in Henning Mankell's Before the Frost. Issue 1 (2nd January 2021) - Maierhofer, Waltraud
ABSTRACT: This article investigates abortion in Sweden and the depiction of abortion attitudes in the bestselling crime novel Before the Frost (2002) by the internationally acclaimed Swedish writer Henning Mankell in which a man murders women who had an abortion as a major step in his plan of religious revival. It will first review the Swedish abortion law, statistics, and sociological research in order to provide additional background on the history and politics of abortion in Sweden, then show that the novel's dialogues realistically reflects the majority of the population's liberal view of induced abortion as a woman's right supported by the law. I argue that the anti-abortion murders turn out to be the criminal plan's flaw because the inspector solves the murders and prevents the main goal, suicide attacks on Swedish churches and possibly more. The line-up of the plot to the showdown in the early days of September 2001 connects the novel with global terrorism and responses to 9/11 resulting in a message about taking religious motivations seriously. In addition, I highlight the connection between the issue of terrorism and the theme of suicide which runs through the novel.